Community health worker in hard-to-reach rural areas of Myanmar: filling primary health care service gaps. Issue 1 (December 2016) - Sommanustweechai, Angkana; Putthasri, Weerasak; Nwe, Mya; Aung, Saw; Theint, Mya; Tangcharoensathien, Viroj; Wynn, San
Abstract Background Myanmar is classified as critical shortage of health workforce. In responses to limited number of trained health workforce in the hard-to-reach and remote areas, the MOH trained the Community Health Worker (CHW) as health volunteers serving these communities on a pro bono basis. This study aimed to assess the socio-economic profiles, contributions of CHW to primary health care services and their needs for supports to maintain their quality contributions in rural hard to reach areas in Myanmar. Methods In 2013, cross-sectional census survey was conducted on all three groups of CHW classified by their training dates: (1) prior to 2000, (2) between 2000 and 2011, and (3) more recently trained in 2012, who are still working in 21 townships of 17 states and regions in Myanmar, using a self-administered questionnaire survey in the Burmese language. Findings The total 715 CHWs from 21 townships had completely responded to the questionnaire. CHWs were trained to support the work of midwives in the sub-centres and health assistant and midwives in rural health centres (RHCs) such as community mobilization for immunization, advocates of safe water and sanitation, and general health education and health awareness for the citizens. CHWs were able to provide some of the services by themselves, such as treatment of simple illnesses, and they provided services to 62 patients in the last 6 months. Their contributions to primary health care services were well accepted by the communities as they are geographically and culturally accessible. However, supports from the RHC were inadequate in particular technical supervision, as well as replenishment of CHW kits and financial support for their work and transportation. In practice, 6 % of service provided by CHWs was funded by the community and 22 % by the patients. The CHW's confidence in providing health services was positively associated with their age, education, and more recent training. A majority of them intended to serve as a CHW for more than the next 5 years which was determined by their ages, confidence, and training batch. Conclusions CHWs are the health volunteers in the community supporting the midwives in hard-to-reach areas; given their contributions and easy access, policies to strengthen support to sustain their contributions and ensure the quality of services are recommended.